THE GEOCHEMICAL SIGNATURE OF THE ELANG PORPHYRY CU-AU DEPOSIT SUMBAWA, NUSA TENGGARA BARAT, INDONESIA - Bastian, Arief; Basuki, Nurcahyo Indro; R, Yan Rizal (Bulletin of Geology, 2024)
The demand for copper and gold has increased significantly, but finding new exposed porphyry deposits has become more challenging. Elang porphyry Cu-Au deposit is one of few world class deposits, discovered in the last 30 years, located in Sumbawa Island, Indonesia. This study aimsto understand the correlation between geochemical elements in porphyry mineralization using soil and core sample data. The research methods include collecting soil and core samples, conducting geochemical analysis, and processing and interpreting the data. The research results show that The Cu-Au mineralization at Elang is mainly within and around multiple tonalite intrusions where intense of early quartz-sulphide and potassic alteration dominates, constrained by the extent of advanced argillic alteration.Tonalite is distinguished based on cross-cutting relationships, texture, and the crystal shape of quartz eye that is present as a phenocryst. The crystalline shapes are closely aligned with the copper and gold mineralization. Variations in the styles of geology and mineralization contribute to differing geochemical expressions of the porphyry deposits. Geochemical data, especially from soil samples, emerges as a valuable method for identifying signatures within porphyry mineralization deposits. The copper,zinc, lead, and molybdenum clearly point to the central of the porphyry system, while broad zones of high gold anomalies are associated with epithermal high-sulfidation systems. Analysis of core samples reveals that the Cu/Au ratio exhibits a distinct vertical zonation pattern throughout the porphyry body. Understanding the geology and geochemical characteristics of the Elang deposit provides valuable insights for exploration strategies aimed at discovering similar deposits elsewhere. Key words: porphyry Cu-Au, geochemical soil anomaly, Elang deposits